2007
DOI: 10.1002/pca.962
|View full text |Cite
|
Sign up to set email alerts
|

Application of atmospheric pressure chemical ionisation mass spectrometry in the identification and differentiation of Panax Species

Abstract: An HPLC-MS method using an atmospheric pressure chemical ionisation (APCI) source has been developed to assist in the differentiation of three ginseng species: Panax quinquefolium (American ginseng), P. ginseng (Chinese ginseng) and P. notoginseng (sanqi) species. The differentiation method relies on the identification of ginsenosides Rf and F11 and notoginsenoside R1. R1 is observed in both P. notoginseng and Chinese ginseng, whilst F1, is found exclusively in the American species. The presence of these compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…5) depicted the abundance of a marker ion at m/z 801.5012 (RT 5.38 min) over 27 samples. This ion fulfilled the criterion of a marker ion because of the unique presence in the American ginseng but not the others [37].…”
Section: Pcamentioning
confidence: 97%
“…5) depicted the abundance of a marker ion at m/z 801.5012 (RT 5.38 min) over 27 samples. This ion fulfilled the criterion of a marker ion because of the unique presence in the American ginseng but not the others [37].…”
Section: Pcamentioning
confidence: 97%
“…Both ginseng and sanqi are commonly used for the treatment of coronary heart disease and cerebral vascular disease [2][3][4] . Belonging to the same genus, ginseng and sanqi possess similar constituents, including their unique active ingredients, ginsenosides [5,6] . Cumulated research outcomes have indicated that identical and variable ginsenosides in these 2 herbs are possibly responsible for the comparable and distinct therapeutic effects between ginseng and sanqi [7] .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these compounds permitted the definitive identification of the species. This technique might provide an alternative approach to analyzing high molecular weight polar compounds that are typically encountered in complex matrices of Chinese medicinal materials [218]. Recently, a fast SPE-HPLC-MS n method was presented for quantitative determination of 3-(3,4-dihydroxyphenyl)-2-hydroxylpropionic acid (Danshensu) from Compound Danshen Dripping Pills in rabbits' heart, liver, kidney, and lung and for qualitative analysis of the bioactive metabolites of Radix Salvia miltiorrhizae from Compound Danshen Dripping Pills in these tissues [219].…”
Section: Dad-esi-msmentioning
confidence: 99%